2013
DOI: 10.20855/ijav.2013.18.4330
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ground Vibrations Induced by Urban Railway Traffic: An Analysis of the Coupling Assumptions Between Vehicle, Track, Soil, and Buildings

Abstract: This paper is concerned with the problem of ground vibrations induced by railway traffic and its modelling through a decoupled approach, using only the finite element modelling for evaluating the ground waves propagation. The vehicle/track dynamics is calculated separately. An important modelling aspect is undoubtedly the track/soil interaction, which can play an important role in the generation of seismic waves. To avoid excessive computational resources, a coupled lumped mass model (CLM model) of the soil ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…These irregularities are most often encountered in traditional tracks, and more typically in urban environments (Figure 18(a)). Taking into account the wheel curvature (Figure 18(b)), analytical functions can be deduced in order to accurately present the legitimate raising of a wheel's contact point [127]. For more modern use, particularly where higher speeds are required, the lengths of the rail may be welded together to form continuous welded rails (CWR).…”
Section: Singular Rail Surface Defectsmentioning
confidence: 99%
“…These irregularities are most often encountered in traditional tracks, and more typically in urban environments (Figure 18(a)). Taking into account the wheel curvature (Figure 18(b)), analytical functions can be deduced in order to accurately present the legitimate raising of a wheel's contact point [127]. For more modern use, particularly where higher speeds are required, the lengths of the rail may be welded together to form continuous welded rails (CWR).…”
Section: Singular Rail Surface Defectsmentioning
confidence: 99%
“…Furthermore, on other types of line (e.g. tram [25] and freight [26]), it has been shown that it is more important to model the vehicle with increased degrees of freedom. [27] Ground vibrations generated by railways have different propagation characteristics depending on the track, soil and vehicle characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is defined as a flexible beam (Young modulus E r , geometrical moment of inertia I r , section A r and density ρ r ) discretely supported by the sleepers (of mass m and with spacing d), including viscoelastic elements for the ballast (stiffness k b and damping coefficient d b ) and the railpads (stiffness k p and damping coefficient d p ). To take into account the dynamic behaviour of the foundation, which plays an important role at low frequencies, a coupled lumped mass (CLM) model is added to the track model, with interconnection elements for the foundation-to-foundation coupling [22]. A C++ object-oriented program was developed, using the in-house EasyDyn library [23].…”
Section: Numerical Modelmentioning
confidence: 99%